Epiphytic bryozoan community of Posidonia oceanica (L.) Delile leaves in two different meadows at disturbed and control locations - KOCAK, F.; AYDIN-ONEN, S. (Mediterranean Marine Science, 2014)
<!--[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The impact of fish farming activities on Posidonia oceanica meadows in the Aegean Sea have been detected by using bryozoan epiphytes as indicators of disturbance. Samples were collected by SCUBA diving in September 2004 for comparing assemblages between disturbed (I1:0-5 m; I2:5-10 m and I3:10-15 m) and control meadows (C1:0-5 m; C2:5-10 m and C3:10-15 m) located at different depths. Regarding to mean percentage cover of bryozoans, significant differences were found between stations, leaf sides, depths and their interactions (p<0.05). Bryozoan species were colonized densely on back side of the adult leaves. Bantariella verticillata, Alcyonidium sp., Aetea truncata, Chorizopora brongniartii, Fenestrulina joannae were frequently observed species on P. oceanica leaves. B. verticillata showed statistically significant side and station differences while other species showed only significant side differences. Moreover, the mean coverage of Aetea truncata showed neither station nor side variations. B. verticillata could be evaluated as an appropriate key species for environmental changes. In the impacted meadow, higher mean coverage values of the species were particularly determined on front side of the leaves. These results suggest that characteristics of localities, leaf sides and leaf parts can be responsible factors on coverage value of epiphytic bryozoan species.